2015
DOI: 10.4103/1735-9066.164504
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cardiac rehabilitation on quality of life in patients with acute coronary syndrome

Abstract: Background:Acute coronary syndrome is one of the major cardiovascular diseases that leads to a significant amount of morbidity. The purpose of the present study was to investigate the effect of cardiac rehabilitation on quality of life in patients with acute coronary syndrome.Materials and Methods:This was a clinical trial study conducted on 50 patients with acute coronary syndrome admitted to the coronary care units of Shohada Hospital in Isfahan in 2013-2014. The participants were randomly assigned to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our findings correspond with the results of many earlier studies that demonstrated improvements in the MCS, PCS, and all the subdomains of the SF-36. Khalife-Zadeh et al [ 17 ] reported that patient awareness of the principles of rehabilitation and gradual resumption of activities improved both physical and mental health indices. Duarte et al [ 18 ] reported regarding the importance of a comprehensive CRP owing to its positive impact on physical health, anxiety, depression, and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings correspond with the results of many earlier studies that demonstrated improvements in the MCS, PCS, and all the subdomains of the SF-36. Khalife-Zadeh et al [ 17 ] reported that patient awareness of the principles of rehabilitation and gradual resumption of activities improved both physical and mental health indices. Duarte et al [ 18 ] reported regarding the importance of a comprehensive CRP owing to its positive impact on physical health, anxiety, depression, and sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…6 Data from Iran corroborate the benefits of CR. [7][8][9][10] Unfortunately, CR is underused, particularly when compared with other secondary prevention recommendations for CVD. 11 Studies conducted in Iran also demonstrate gross under-referral, enrolment, adherence and completion.…”
Section: Introductionmentioning
confidence: 99%